The Status of women in Philippine society [videorecroding] traditions, realities, prospects - Kintanar, Thelma B. (The Center, 1990)
Documents prospects for women in Philippine society, the considerable gains they made in the last decade such as the formulation of Philippine Development Plan for Women, 1989-1992, the passing of pro-women laws as well as gains in organizing education and research.